Effects of Communication Strategies Instruction by Using Task–based Learning for Speaking Proficiency of Students majoring in English Education at Roi Et Rajabhat University - ทองปาน อังชรินทร์; ศรีพิบูลย์ รัชฏาพร (Journal of Roi Et Rajabhat University, 2016)
The purposes of this research were to 1) compare English speaking proficiency of English majors before and after being taught communication strategies using task–based learning, 2) compare the use of communication strategies before and after being taught using task–based learning, and 3) explore students’ opinions toward instruction using task–based learning. The samples of this research consisted of the purposive sampling of a selected class of 30, English majors in the second semester of the 2015 academic year. The experiment lasted 8 weeks with 3 periods a week. The instruments for the experiment were 8 lesson plans, a speaking proficiency test, a set of communication strategies, an observation form, and a questionnaire. The data were analyzed by paired t–test, percentage, frequency, mean and standard deviation. The findings were as follows: 1. The students’ speaking proficiency after receiving communication strategy instruction using task–based learning was significantly higher than the proficiency before at the 0.05 level. 2. The students taught communication strategies using task–based learning used more communication strategies after the experiment than before the experiment. 3. The students’ opinions toward communication strategy instruction using task– based learning were highly positive.